Modulation of visual-motor responses by the perception of object affordance, automatic imitation and action agency - Pereira Lima, R (2018)
When we interact with the environment in our everyday life the relationship between what we see and what we do is under continuous coupling, i.e., our perceptions and actions are built through a continuous reciprocal flow of information between sensory and motor processes. This thesis reports a series of experiments investigating perception-action coupling in terms of modulation of response selection and execution processes by the perception of object affordances, automatic imitation and action agency. In Chapter 2, I focused on demonstrating the automaticity of the action priming effect directing attention and its relationship with awareness of object affordances. Different from the classical studies on object affordances, I addressed this relationship through attentional effects to avoid SRC effects as a confound. The result suggested that, at least for error rates, when the relationship between an object and its action-related stimulus is explicit, affordances can elicit an attentional bias towards a representation of the action that a recently seen object affords. In Chapter 3, I investigated the temporal aspects of automatic imitation focusing on the discussion regarding the stage of information processing where the interfering effects of observing an incongruent action takes place. The results demonstrated that the automatic imitation effect interferes not only with response selection but also with response execution, therefore providing new evidence of the reach of perception-action coupling effects. In Chapter 4, I investigated the role of a prominent self-stimulus and the sense of agency in the automatic imitation effect. The results clearly demonstrated that automatic imitation effects can be modulated as a function of self-related information, reducing sensitivity to observed movements as a consequence of self-focus. Overall, this thesis demonstrated a strong relationship between perception and action affecting the response process. Actions can be primed by the perception of either object affordance properties or by the perception of actions performed by others.